1997
DOI: 10.1063/1.869352
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian moment reduction for describing vortices in shear

Abstract: This paper discusses a general method for approximating two-dimensional and quasigeostrophic three-dimensional fluid flows that are dominated by coherent lumps of vorticity. The method is based upon the noncanonical Hamiltonian structure of the ideal fluid and uses special functionals of the vorticity as dynamical variables. It permits the extraction of exact or approximate finite degree-of-freedom Hamiltonian systems from the partial differential equations that describe vortex dynamics. We give examples in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 22 publications
2
68
0
Order By: Relevance
“…II) is somewhat different in flavor from the others. Imagine that you have succeeded in obtaining a finite Hamiltonian system out of some fluid model, the Kida vortex being a good example (see, for example, Meacham et al, 1997). What should you expect of the dynamics?…”
Section: Introductionmentioning
confidence: 99%
“…II) is somewhat different in flavor from the others. Imagine that you have succeeded in obtaining a finite Hamiltonian system out of some fluid model, the Kida vortex being a good example (see, for example, Meacham et al, 1997). What should you expect of the dynamics?…”
Section: Introductionmentioning
confidence: 99%
“…Meacham et al (1994) further generalised the ellipsoidal model to include a uniform background horizontal and vertical shear. Meacham et al (1997) showed that the time-dependent vortex motion (which is potentially chaotic) can be described exactly in terms of a finite degreeof-freedom model obtained from the method of 'Hamiltonian moment reduction'. The stability of QG ellipsoidal vortices has been studied for some special background flows, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these ellipsoidal solutions have been studied by numerous authors, cf. Meacham et al (1994), Meacham, Morrison & Flierl (1997), Miyazaki, Ueno & Shimonishi (1999), Hashimoto, Shimonishi &McKiver &.…”
Section: Introductionmentioning
confidence: 99%